The geographic distribution of Pluteus xylophilus (Pluteaceae) in the Americas - Tincani, Matías Sebastián; Niveiro, Nicolás; Salvador-Montoya, Carlos Alberto (Phytotaxa, 2025)
Pluteus xylophilus (Speg.) Singer (1951: 405) is a lignicolous species of the section Pluteus Fr. (1836: 338). It is characterized by a large, plano-convex pileus with a pale gray to grayish brown pileal surface, center often with a broad, low to high umbo, covered with indistinct brown to grayish brown fibrils (darker in the center and paler towards the margin) discoloring radially towards the margin, a cream central stipe with a clavate base and appressed brown fibrils (increasing towards the base), free, crowded and pinkish lamellae, pink spore print, and absence of annulus and volva (Ramírez-Guillén & Guzman 2003, Meijer 2008, Menolli & Capelari 2014, Menolli et al. 2010, 2015). Micromorphologically, this species has broadly ellipsoid to elongate, hyaline, smooth, thick-walled, inamyloid basidiospores, a hymenium with three types of pleurocystidia and dimorphic cheilocystidia, the context composed of inflated and septate, slightly thick-walled hyphae, and a pileipellis, a repent epicutis composed of septate, and elongate, slightly thick to thin-walled hyphae (Singer 1951, 1958, Menolli & Capelari 2014, Menolli et al. 2015). Pluteus xylophilus has a Neotropical distribution with records in Argentina, Bolivia, Brazil, Mexico, Peru, Colombia, and Chile (Spegazzini 1925, Singer & Digilio 1951, Singer 1958, Stijve & Meijer 1993, Valenzuela 2003, Meijer 2006, 2008, Menolli et al. 2015).